GERAKAN 1.000 MASKER UNTUK PENCEGAHAN VIRUS COVID 19 DI PASAR YADNYA DESA ADAT KESIMAN DENPASAR TIMUR - Putu Astri Lestari; Made Arini Hanindharputri; Ni Putu Emilika Budi Lestari (Jurnal Lentera Widya, 2020)
This community service activity is a collaboration of a team of lecturers and students from the Bali School of Design (STD Bali) and the Academy of Information and Computer Management (AMIK) New Media with the Student Association held in mid-April precisely on April 18, 2020, at the Yadnya Market, Kesiman Traditional Village Kesiman Village, East Denpasar District. This activity received a very good reception from the Yadnya Market and also the Traditional Village of Kesiman. Distribution of 1000 Masks in the Yadnya Kesiman Market environment is a form of community service in STD Bali and AMIK New Media in participating in preventing and breaking the chain of the spread of Covid Virus 10. Some of the factors supporting this activity include: STD Bali Institute Support and AMIK New Media especially the Putra Indonesia Education Foundation in funding activities, STD Bali Campus has a Fashion Design major so it is very helpful in the preparation of 1000 masks to be distributed. In addition, this activity also received full support from Yadnya Market Management and Kesiman Customary Village Management. Some of the obstacles encountered during this activity include: (1) There are limitations in the number of sewing machines used to sew masks on campus so that students sew at home. (2) The existence of the Covid 19 outbreak that caused the sewing process on campus to be slightly hampered because it had to implement Social Distancing. (3) The mask distribution activities cannot be handed over directly to traders in the Yadnya Market to avoid the crowds of the community, so the surrender is carried out symbolically to the Head of the Yadnya Market